Maritime security in East and Southeast Asia : political challenges in Asian waters - Tarling , Nicholas ; Chen, Xin (Palgrave Macmillan, 2020)
Contents: 1. Introduction -- 2. Maritime Security and Piracy -- 3. The Straits of Malacca: Malaysia’s Threat Perception and Strategy for Maritime Security -- 4. Securitising Piracy and Maritime Terrorism along the Malacca and Singapore Straits: Singapore and the Importance of Facilitating Factors -- 5. The Challenges of Maritime Security Cooperation in the Straits of Malacca: Another Singapore Perspective -- 6. The Seas of Our Insecurity: Ordinary versus State Discourses on Maritime and Human Security in the Philippines -- 7. Japan’s Maritime Security—Continuity and Post-Cold War Evolution -- 8. Charting Thailand’s Maritime Security Policies from 1932 to 2012: A Liberal International Relations Perspective -- 9. Sea Power and Maritime Disputes: China’s Internal Discourses.